DENTAL AND ORAL HEALTH CARE MODEL IN PEDIATRIC PATIENT - Muh. Alfi Syahrin Jalil; Endah Aryati Eko Ningtyas; Bedjo Santoso (JDHT Journal of Dental Hygiene and Therapy, 2023)
Background: Basic Health Research in 2018 stated that 57.6% of the Indonesian population had dental and oral health problems with the largest proportion in the 5-9 year old group at 67.3%, 10-14 year olds 55.6%. The presentation of caries in primary teeth and permanent teeth in children is 62-65.8%. Factors that cause dental caries are influenced by the behavior of children who do not maintain oral hygiene, amounting to 2.8% in Indonesia, because children have characteristics that are not yet capable of being responsible for doing things, so they need treatment. Objective: Develop a model design, carry out expert validation tests for feasibility and prove that the dental and oral health care service model is effective in an effort to reduce the anxiety level of pediatric patients in treatment. Method: Research and Development with a Quasy experimental Pretest-Posttest group design. The sampling technique used purposive sampling for Dental and Oral Therapists and Child Patients at RSGM UNIMUS. 10 Dental and Oral Therapists intervened, 11 child patients were given the Care Model Results of Development and Control, 10 Dental and Oral Therapists, 11 child patients at RSGM Unimus were given the 2006 Minister of Health Decree 284 Care Model. Data collection techniques in this research were interviews, pre-test and post-test. The validity of expert data was tested using the Intraclass Correlation Coefficient (ICC) and the effectiveness of the model was tested using Wilcoxon and Mann-Whitney. Results: The dental and oral health care model for pediatric patients is suitable as dental and oral health care for pediatric patients in specialist pediatric dentistry clinics with expert validation results of p 0.002, knowledge of Dental and Oral Therapists with a value of ?=3.90, attitude ?=23.50 , skills ?=4.20, pediatric patient anxiety ?=14.36, pediatric patient satisfaction ?=18.36. Conclusion: The dental and oral health service model is feasible and effective in reducing the anxiety level of pediatric patients during treatment